Biomimetic non-linear CMOS adder for neuromorphic circuits - Xiahan Zhou; Yimu Guo; Parker, Alice C.; Chih-Chieh Hsu; Choma, John (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
This paper presents a novel biomimetic CMOS two-input non-linear adder circuit to fully emulate computations within dendritic branches of pyramidal neurons. It automatically and dynamically adjusts neuron responses based on the input magnitudes of EPSP potentials. The design is based on CMOS 180nm technology with dual power supplies.